Clinical bacteriology - Struthers, J. Keith, ....-; Westran, Roger P., ....- (London : Manson, 2005)
In this brief, beautifully illustrated book, the authors introduce the reader to the basic science of medical microbiology and relate it to clinical practice. Integrating concise text, over 270 full-colour diagrams and selected photomicrographs, they provide an understanding of bacterial infection and give the reader the necessary grounding to select the right antibiotics and follow logical diagnostic and management strategies. Following introductory chapters on the nature, structure and function of bacteria, the principles are then applied to each body system in turn, dealing with organisms, pathogenesis, diagnosis, treatment and public health. There are also chapters on infection control emphasising the importance of good hygiene in preventing hospital acquired infection. In the context of new problem-based curricula, the book will be welcomed especially by medical students, trainee physicians and microbiologists, laboratory biomedical scientists and nurses working in infection control.
Keywords: Bacteriologie; Medische microbiologie